A mechanistic model for denitrifying anaerobic methane oxidation coupled to dissimilatory nitrate reduction to ammonium. (January 2022) - Peng, Lai; Nie, Wen-Bo; Ding, Jie; Xu, Yifeng; Li, Qi; Yu, Siwei; Ren, Nan-Qi; Xie, Guo-Jun
Abstract: Nitrate/nitrite-dependent anaerobic methane oxidation (n-DAMO) is an important process linking nitrogen and carbon cycle. It is recently demonstrated that n-DAMO archaea are able to couple n-DAMO to dissimilatory nitrate reduction to ammonium (DNRA). In this work, a mathematical model is developed to describe DNRA by n-DAMO archaea for the first time. The anabolic and catabolic processes of n-DAMO archaea, n-DAMO bacteria and anaerobic ammonium oxidation (Anammox) bacteria are involved. The different impacts of exogenous and endogenous nitrite on DNRA and n-DAMO microbes are considered. The developed model is calibrated and validated using experimental data collected from a sequencing batch reactor (SBR) and a counter-diffusion membrane biofilm bioreactor (MBfR). The model outputs fit well with the profiles of nitrogen (N) dynamics and biomass changes in both reactors, demonstrating its good predictive ability. The developed model is further used to simulate the counter-diffusion MBfR incorporating n-DAMO and Anammox process to treat sidestream wastewater. The simulated distribution profiles of N removal/production rates by different microbes along biofilm depth reveal that DNRA by n-DAMO archaea plays an important role in N transformation of the integrated n-DAMO and Anammox process. It is further suggested that the counter-diffusion MBfR under the investigated conditions should be operated at proper hydraulic retention times (HRTs) (i.e. 6h and 8h) with exogenous NO2 − in the range of 0–10 mg N/L or at HRTs >3h with the absence of exogenous NO2 − in order to achieve dischargeable effluent. Graphical abstract: Image 1 Highlights: A mathematical model is developed to describe DNRA by n-DAMO archaea. The impacts of intra- and extra-cellular nitrite on DNRA and microbes are modeled. The model predictions fit well with experimental data from a SBR and a MBfR. Both HRT and influent nitrite regulate the N removal in the MBfR.